Kajian Yuridis Terhadap Tindak Pidana Penyalahgunaan Narkotika - Nurdia, Nurdia; Balla, Herman; Suardi, Suardi (Jurnal Litigasi Amsir, 2023)
The purpose of this research was conducted: To find out the judge’s considerations in passing a decision on the crime of narcotics abuse, decision number: 19/Pid.Sus/2022.PN.Enrekang; & To Know the Application of Material Criminal Law Against the Crime of Narcotics Abuse Against Decision Number: 19/Pid.Sus/2022.PN.Enrekang. The type of research used is Normative Legal Research. The results of the study: As for the legal considerations by the Judge of the crime regarding Every Narcotics Abuse of Group I for himself is punished with a maximum imprisonment of 4 (four) years in decision Number: 19/Pid.Sus/2022.PN.Enrekang, in dropping the sentence was appropriate because the Judge had considered several things, both in terms of Juridical Facts and Subjectively which included accountability for the actions committed with the consideration that when carrying out his actions, the defendant was aware of the consequences. In addition to the above, the Judge also did not see any justification or excuse that could eliminate the unlawful nature of the Defendant’s actions. The Panel of Judges saw that the things that were aggravating were that the Defendant’s actions did not support the Government’s program to eradicate the distribution and use of Narcotics illegally, the Defendant’s actions could damage himself and other young people, and the Defendant had been convicted before; & Application of material criminal law by judges against criminal acts regarding Every Narcotics Abuser Group I for himself is sentenced to imprisonment for a maximum of 4 (four) years in the Decision mentioned above, and it is appropriate for the Public Prosecutor to use 2 (two) charges, namely: Primary Article 112 Paragraph of Law No. 35 of 2009 concerning Narcotics in conjunction with Article 132 (1) of Law No. 35 of 2009 concerning Narcotics, and Subsidiaries of Article 127 paragraph (1) of the Narcotics Act No. 35 of 2009 about Narcotics. Among the elements of the two articles charged by the Public Prosecutor, what has been proven legally and convincingly guilty is Article 127 Paragraph (1) letter of Law No. 35 of 2009 concerning Narcotics where the acts and elements of the Articles match each other.